Delivering Effective Behaviour Support in Schools : a Practical Guide. - Barrow, Giles (Taylor and Francis, 2013)
This book is intended to help schools become increasingly inclusive. The advice and guidance is aimed at managers and practitioners providing behavior support, either through an LEA service, by outreach work from specialist centers or via on-site provision. You will find advice on developing effective support; planning, monitoring and evaluating support; working in partnership with colleagues in schools and other services; identifying resources to maximize behavior support interventions; and providing support staff with proven techniques for improving service delivery. There ar.
Keywords: Problem children -- Education.; Mainstreaming in education.; EDUCATION -- Special Education -- Social Disabilities.; Mainstreaming in education; Problem children -- Education